Analysis of Batrsiyia Product Sales Prediction Using Linear Regression Method - Priana, Firzi Cahya; Danny, Muhtajuddin; Edora, Edora (Journal of Computer Networks, Architecture and High Performance Computing, 2025)
The rapidly growing herbal and health industry encourages the need for accurate sales planning to avoid the risk of shortages or excess stock. This research aims to predict sales of Batrsiyia products using the Linear Regression algorithm with RapidMiner tools, through analyzing historical data such as sales time, number of products sold, and unit prices to identify patterns and trends to produce accurate predictions. The results show that the Linear Regression algorithm is able to predict sales with an RMSE value of 96687030.354 +/- 0.000, and a Squared Error of 9348381838748252.000 +/- 25081062946532056.000. This approach helps companies understand sales patterns, predict future trends, and optimize stock and marketing strategies. By utilizing data mining-based prediction methods, companies can make more informed decisions in meeting customer needs, maintaining business stability, and improving operational efficiency.